The fifth gospel - Caldwell, Ian, 1976- (New York : Simon & Schuster, 2015)
A lost gospel, a contentious relic, and a dying pope's final wish converge to send two brothers--both Vatican priests--on an intellectual quest to untangle Christianity's greatest historical mystery.
Keywords: Jesus Christ -- Relics -- Fiction; Catholic Church -- Fiction; Clergy -- Fiction; Apocryphal Gospels -- Fiction; Murder -- Fiction; Mystery fiction; Suspense fiction